2013
DOI: 10.1080/08927022.2013.839871
|View full text |Cite
|
Sign up to set email alerts
|

DL_MONTE: a general purpose program for parallel Monte Carlo simulation

Abstract: Monte Carlo (MC) represents a powerful simulation tool that can be usefully applied to calculating thermodynamic data. However, such codes are normally bespoke for a particular problem and not widely applicable. In this paper, we report a new flexible and versatile MC code called DL_MONTE, which builds on the highly successful DL_POLY molecular dynamics code to allow the treatment of polymers, minerals, semiconductors and metals in a range of applications on both workstations and highly parallel supercomputers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 55 publications
(56 reference statements)
1
44
0
Order By: Relevance
“…Generalpurpose MC programs that provide access to a wide range of techniques -including advanced techniques for complex systems -have been lacking. As far as we are aware there are only a handful of general-purpose MC programs available to the community [30][31][32][33][34], and of these, only Casandra [30] and DL MONTE [34] are under active development. However, the development of such programs is essential if the unique capabilities of MC are to be fully exploited by the scientific community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalpurpose MC programs that provide access to a wide range of techniques -including advanced techniques for complex systems -have been lacking. As far as we are aware there are only a handful of general-purpose MC programs available to the community [30][31][32][33][34], and of these, only Casandra [30] and DL MONTE [34] are under active development. However, the development of such programs is essential if the unique capabilities of MC are to be fully exploited by the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we present DL MONTE (version 2), with particular emphasis on the extensive functionality which has been added to the program since the release of version 1 in 2013 [34]. The most important additions include the lattice-switch MC method; and the widely-used methods for calculating free energy profiles -hereafter collectively referred to as free energy difference (FED) methods -which can be used in conjunction with replica-exchange parallel tempering.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that mixing rules applied to CO 2 ‐zeolite interactions yielded overestimated isotherms at low pressures and underestimated isotherms at high pressure. Crossing of the isotherm resulting from MD simulations with the one resulting from experiment demonstrates a qualitatively correct behavior from using mixing rules . The qualitatively correct behavior may originate from the general nature of the force zeolite force field and its transferability to other surfaces and interfaces.…”
Section: Computational Detailsmentioning
confidence: 77%
“…The CLAYFF‐based zeolite force field used was constructed by primarily fitting to structural experimental data of zeolite . Hence, there was no focus on reproducing the dynamics of the surface.…”
Section: Computational Detailsmentioning
confidence: 99%
“…4 We describe how LSMC can be used to evaluate interfacial free energies in Section 8. 5 Specifically, LSMC is earmarked for inclusion in the general-purpose Monte Carlo code DL MONTE [26]. 6 Of course, in doing this the user's module is free to interface with 'external' modules, or even external programs.…”
Section: Introductionmentioning
confidence: 99%